Effectiveness of dolutegravir-based regimens compared to raltegravir-, elvitegravir-, bictegravir, and darunavir-based regimens among older adults with HIV in the Veterans Aging Cohort Study (VACS) - Lei Yan; Cassidy E. Henegar; Vincent C. Marconi; Kirsha S. Gordon; Charles Hicks; Vani Vannappagari; Amy C. Justice; Mihaela Aslan (AIDS Research and Therapy)
Abstract Background Real-world data on treatment patterns and clinical outcomes for newer drugs, including integrase strand transfer inhibitors, among older people with human immunodeficiency virus (PWH) are limited. Methods This cohort study included PWH enrolled in the Veterans Aging Cohort Study (VACS) who were prescribed a standard 3-drug antiretroviral therapy (ART) regimen containing dolutegravir (DTG), bictegravir (BIC), cobicistat boosted elvitegravir (EVG), raltegravir (RAL), or darunavir/ritonavir (DRV) plus 2 nucleoside reverse transcriptase inhibitors between January 1, 2014, and March 31, 2020, and who were ≥50 years at regimen initiation. The association between regimen and virologic effectiveness or discontinuation was assessed using logistic regression models with inverse probability of treatment weights. Pairwise comparisons were made between DTG-based regimen and each of the other 3-drug regimens, stratified by ART experience. Results Among 15,702 PWH (across treatment groups, median age 58–62 years; 94–98% male; 5–11% Hispanic; 44–60% Black; 29–42% White), 5,800 received DTG-based regimens, 2,081 BIC-based regimens, 4,159 EVG-based regimens, 1,607 RAL-based regimens, and 2,055 received DRV-based regimens. Among ART-naïve PWH, there were no statistical differences in the odds of virologic suppression, and 6- and 12-month discontinuations were higher in those on DRV. Among ART-experienced PWH, compared to DTG, those on RAL and DRV were less likely to be suppressed at 6 months (RAL vs DTG: aOR 0.64, 95% CI 0.51–0.81; DRV vs DTG: aOR 0.63, 95% CI 0.51–0.76) and those on EVG and DRV were less likely suppressed at 12 months (EVG vs DTG: aOR 0.82, 95% CI 0.68–0.99; DRV vs DTG: aOR 0.64, 95% CI 0.52–0.80). Those on DRV were more likely to have virologic failure within 12 months (aOR 1.96, 95% CI 1.30–2.97). Six- and 12-month discontinuations were higher in those on RAL and DRV, but less likely for BIC-based regimens. Conclusions DTG-based regimens demonstrated higher levels of effectiveness and durability compared to DRV- or RAL-based regimens and had similar treatment responses as BIC- and EVG-based regimens among ART-experienced older PWH.